The Legal Status of Mut’ah Marriage in Indonesia - Mimin mintarsih; Lukman Mahdami (Jurnal Penelitian Hukum De Jure, 2021)
Mut'ah marriages with contract marriages bring a dilemma to society. The society views that this is halal (lawful) and legal, but in essence it does not carry out rights and obligations. The problem of this paper is how do civil cases (of mut'ah marriage) get legal certainty so that the logic of "urgent" becomes a status that can protect the rights and dignity of married couples in Indonesia? The purpose of this paper is to analyze the status of mut'ah marriage law so that it does not become a political contribution in Indonesia. The research method used is normative juridical. The result of this research is that in relation to the basis for practice of mut'ah which is considered an emergency, it is clearly contrary to Islamic law because the real aim and purpose of marriage are permanent. Mut'ah actually destroys human civilization and ethics or implies bad faith. The harm will befall the offspring. Children who are born have no legal certainty because they are considered children born of adultery. This research concludes that mut'ah is contrary to the basic provisions of the Material Law of the Religious Courts on Marriage which strictly prohibits mut'ah marriages (Article 2 paragraph 2 of Law No. 1 Year 1974 concerning marriage), the criminal sanctions are regulated in the Draft Law on the Religious Courts of Marriage Article 39 because it is not recorded and Article 144 concerning sanctions against the perpetrator, and the marriage is null and void by law.